2015
DOI: 10.1183/13993003.01319-2015
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery diameter to predict pulmonary hypertension in pulmonary sarcoidosis

Abstract: Pulmonary hypertension (PH) is a known complication of pulmonary sarcoidosis with a prevalence ranging from 5% to 74% [1]. The aetiology of PH in sarcoidosis is not fully understood. Usually, it is attributed to the destruction of the distal capillary bed by lung fibrosis and/or chronic hypoxaemia. However, the severity of PH does not correlate consistently with the degree of pulmonary fibrosis, and PH exists in sarcoidosis patients without fibrosis, suggesting a multifactorial mechanism. The presence of PH is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…Forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and DLCO are generally lower in SAPH compared with sarcoidosis patients without PH. 6,7,11,18,21,60 DLCO seems to be the strongest independent predictor. 18,21 As mentioned earlier, destruction of the alveoli and loss of pulmonary capillary volume due to fibrosis and muscle cell proliferation are believed to cause reduction of the DLCO.…”
Section: Pulmonary Function Testsmentioning
confidence: 88%
See 2 more Smart Citations
“…Forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and DLCO are generally lower in SAPH compared with sarcoidosis patients without PH. 6,7,11,18,21,60 DLCO seems to be the strongest independent predictor. 18,21 As mentioned earlier, destruction of the alveoli and loss of pulmonary capillary volume due to fibrosis and muscle cell proliferation are believed to cause reduction of the DLCO.…”
Section: Pulmonary Function Testsmentioning
confidence: 88%
“…Positive correlation with mean PAP has been described in patients with lung disease [66][67][68] ; however, the presence of fibrotic lung disease complicates the accuracy of these measurements. 60,69,70 Huitema et al studied sarcoidosis patients only, and found a good correlation between the pulmonary artery diameter indexed for body surface area and presence of PH. 60 Other chest CT parameters can be indicative for the presence of PH, such as segmental artery to bronchus ratio >1 or right ventricular enlargement, but they have not shown any valuable correlation for clinical practice.…”
Section: Chest Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…99 Correcting for body mass index may improve the predictability of this ratio. 100 However, not all groups have found the ratio as reliable in SAPH. 101 Transthoracic echocardiogram (TTE) is one of the most widely used tests to assess for pulmonary hypertension.…”
Section: Screeningmentioning
confidence: 99%
“…Recently, there has been significant interest in the use of CT in COPD, with several studies evaluating the utility of the ratio of the pulmonary artery to ascending aortic diameter (PA:A ratio) and pulmonary arterial enlargement [1519]. The PA:A has been calculated in several cohorts of healthy patients and those with different chronic respiratory conditions, and correlates with PA pressures as measured by RHC [9, 1517, 2022] and worsening clinical outcomes [15, 17, 18, 20, 21, 2325]. In a cohort of very severe COPD patients, the PA:A correlated with invasive haemodynamics, and a PA:A >1 independently predicted PH defined as a mean PA pressure >25 mmHg at right heart catheterisation with a sensitivity of 73% and a specificity of 84% [16].…”
mentioning
confidence: 99%